Given equation : 45(2x+5)−4=1
45 is in front of parenthesis (2x+5).
So, we need to multiply 45 by (2x+5).
In order to multiply 45 by (2x+5), we need to distribute 45 over (2x+5).
We get, 45*2x + 45*5 = 90x + 225.
Therefore, 45(2x+5)−4=1 equation could be written as
90x + 225 - 4 = 1 in first step.
Now, subtraccting 225-4, we get 221.
In second step 90x + 225 - 4 = 1 can be written as
90x +221 = 1.
Subtractcing 221 from both sides, we get
90x +221 -221 = 1-221.
In third step we can simplify equation to
90x = -220.
Dividing both sides by 90.
90x/90 = -220/90.
In fourth step we get equation,
x = -220/90.
On simplifying fraction -220/90, we get -22/9 and in decimal we get -2.44..
So, final answer is x= -22/9 or -2.44..